2011
DOI: 10.4103/2152-7806.91139
|View full text |Cite
|
Sign up to set email alerts
|

The arcade of Struthers: An anatomical study with potential neurosurgical significance

Abstract: Background:Significant controversy exists regarding the existence of the so-called arcade of Struthers and whether this structure is involved in some cases of proximal ulnar nerve entrapment. Therefore, the aim of the present study was to further elucidate this anatomy.Methods:Fifteen cadavers (30 sides) underwent dissection of the medial arm with special attention to the course of the ulnar nerve and its relationships to the soft tissues of this region.Results:We identified a thickening in the inferior medial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 25 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The results of the study herein suggest that the SA can be found in most individuals, but that its presentation is highly variable, described in Tables 8-11. Al-Qattan and Murray [2], Mirza et al [27], Siqueira and Martins [32] and Tubbs et al [38], all describe at least some occurrence of an atypical SA, differing by the source of the thickened fascia or musculotendinous band. Even more inconsistency lies in the morphology of the SA, where most tended to be musculotendinous, but a large proportion was still found to be solely tendinous or muscular.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the study herein suggest that the SA can be found in most individuals, but that its presentation is highly variable, described in Tables 8-11. Al-Qattan and Murray [2], Mirza et al [27], Siqueira and Martins [32] and Tubbs et al [38], all describe at least some occurrence of an atypical SA, differing by the source of the thickened fascia or musculotendinous band. Even more inconsistency lies in the morphology of the SA, where most tended to be musculotendinous, but a large proportion was still found to be solely tendinous or muscular.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the analysis of the SL, assessment of the SA was divided by subgroups -geographical prevalence, atypical prevalence, atypical type, morphology, relation to the ulnar nerve, and ulnar nerve compression. [38] 2011…”
Section: Prevalence Of the Samentioning
confidence: 99%
See 1 more Smart Citation
“…Mizia et al (8) estimated its prevalence as 53%. Tubbs et al (9) described three types of Struthers' arcade. Type I was described as the most common, where thickening of the brachial fascia formed the arcade.…”
Section: Anatomymentioning
confidence: 99%
“…Type I was described as the most common, where thickening of the brachial fascia formed the arcade. In type II, the arcade is related to the internal brachial ligament (aponeurotic continuation of the brachialis muscle), and type III arcade is due to thickened MIS (9).…”
Section: Anatomymentioning
confidence: 99%